2018
DOI: 10.1021/acs.jpca.8b06118
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of an Alkylidenecarbene by Ultrafast Transient Absorption Spectroscopy

Abstract: Singlet α-methylbenzylidenecarbene has been detected and characterized for the first time by femtosecond transient absorption (fs-TA) spectroscopy. The carbene was generated by photolysis of the hydrocarbon precursor, 1-(1-phenylethylidene)-1a,9b-dihydro-1 H-cyclopropa[ l]-phenanthrene, in acetonitrile. The photolysis initially forms the singlet excited state of the precursor which then extrudes α-methylbenzylidenecarbene in 4.0 ps. The decay of α-methylbenzylidenecarbene, which was previously shown to rearran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“… 11 Besides computational data, 12 , 13 very few data on singlet vinylidenes exist, which are based on matrix isolation 14 , 15 or gas phase spectroscopy. 16 18 Singlet H 2 C=C: has been proposed in combustion processes and rearranges on the picosecond time scale to acetylene. 19 In addition to the singlet state, vinylidenes also feature two symmetry-distinct triplet states of similar energy, which are typically high-lying electronically excited states.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Besides computational data, 12 , 13 very few data on singlet vinylidenes exist, which are based on matrix isolation 14 , 15 or gas phase spectroscopy. 16 18 Singlet H 2 C=C: has been proposed in combustion processes and rearranges on the picosecond time scale to acetylene. 19 In addition to the singlet state, vinylidenes also feature two symmetry-distinct triplet states of similar energy, which are typically high-lying electronically excited states.…”
Section: Introductionmentioning
confidence: 99%
“…The direct observation of carbene reaction pathways has been the subject of several previous studies. 53 61 By monitoring the C=O stretching modes using time-resolved infrared (TRIR) spectroscopy, 54 Xue et al. demonstrated that a variety of ylides could be directly observed from the reaction of the singlet α-carbonyl carbene (2) with nucleophilic solvents such as THF, ACN, and deuterated methanol (MeOD).…”
Section: Introductionmentioning
confidence: 99%
“…2 Measurement of absolute rates of 1,-2-migration requires direct detection of the alkylidene carbene, with Phillips, Hadad and Thamattoor reporting the first observation in solution (PhMeC=C:) by femtosecond spectroscopy, just two years ago. 15 It has long been recognized that some alkylidene β-substituents (RX, RY) have a much greater propensity for 1,2-migration (e.g. H, Aryl, Alkynyl) than others (e.g., Alkyl), [6][7][8] yet only a few studies have sought to explicitly assess this, using isotopic 13 C/ 14 C labelling.…”
Section: Introductionmentioning
confidence: 99%